HUBUNGAN ANTARA DIKLAT BERJENJANG TINGKAT DASAR PENDIDIK PAUD DENGAN PROSES PEMBELAJARAN ANAK USIA DINI DI KECAMATAN GONDANG KABUPATEN MOJOKERTO - Purnamawati, Frimha; Fajarwati, Linda; Levia, Devita Trisna Ayu (Comm-Edu (Community Education Journal), 2024)
Basic level education and training for early childhood educators in Cluster II of Early Childhood Education (PAUD) in Gondang District, Mojokerto Regency, revealed several gaps in the teaching process. These were evidenced by issues such as educators' insufficient application of teaching principles in managing classrooms during learning activities. Consequently, many students fail to pay attention when educators deliver material, resulting in a disruptive classroom atmosphere. Furthermore, there is a lack of effective lesson planning aligned with the curriculum. Thus, research was conducted to address the problem statement: Is there a correlation between hierarchical training for PAUD educators and the early childhood learning process in Gondang District, Mojokerto Regency?. It employed a quantitative approach with correlational research. The study area was purposively chosen within Cluster II of PAUD in Gondang District, Mojokerto Regency, with a total population of 25 educators. Data collection techniques involved questionnaires and documentation, with data analysis conducted using Pearson Product Moment correlation formula. The research's correlation coefficient yielded a result of 0.785, while the critical value r-table was 0.396 at a significance level of 0.05, with N=25. Consequently, the obtained result of r-value > r-table (0.785 > 0.396) led to the conclusion that there is a significant relationship between hierarchical training for PAUD educators and the early childhood learning process in Cluster II of PAUD in Gondang District, Mojokerto Regency, categorized as a strong or high-level relationship.